2020
DOI: 10.9734/ajaees/2020/v38i830398
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Status of Pineapple Growers in Moulvibazar District of Bangladesh

Abstract: Socio-economic indicators are significant for determining the overall lifestyle of the Pineapple Growers. The study examines the different socio-economic variables of the pineapple farmers. The researchers selected the Sreemangal upazila of Moulvibazar district purposively and primary data was collected through a structured questionnaire during 2017-2018 cropping season from one hundred pineapple growers (small, medium and large) following simple random sampling technique. Descriptive statistics include freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
3
1
0
Order By: Relevance
“…The findings indicate that a large proportion (42.6%) of the growers were middle-aged compared to 38.7% young and 18.7% old aged respectively. Almost similar findings were reported by Alam [22], Ali [23], and Datta et al [24] in their respective studies. It might be because young to middle-aged growers comparatively give preference to pineapple cultivation to support their family to the relatively old growers.…”
Section: Selected Characteristics Of the Pineapple Growerssupporting
confidence: 87%
“…The findings indicate that a large proportion (42.6%) of the growers were middle-aged compared to 38.7% young and 18.7% old aged respectively. Almost similar findings were reported by Alam [22], Ali [23], and Datta et al [24] in their respective studies. It might be because young to middle-aged growers comparatively give preference to pineapple cultivation to support their family to the relatively old growers.…”
Section: Selected Characteristics Of the Pineapple Growerssupporting
confidence: 87%
“…It was also observed that medium farmers are more engaged in training achievement than other farmers in the study areas (Table 10). This finding coincides with [8].…”
Section: Training Status Of the Wheat Farmerssupporting
confidence: 87%
“…The age distribution of sample farmers was classified into five age groups (Table 3). Table 3 [8,12,13] also found similar results. However, the average age of the total sampled wheat farmer was 48.97 years.…”
Section: Age Distribution Of the Wheat Farmerssupporting
confidence: 55%
See 1 more Smart Citation